Survey of LEU olympiad 2014 for young mathematicians - Jakaitytė, Eglė; Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2014)
The texts and solutions of the LEU young mathematicians olympiad – 2014 are presented.
Keywords: mathematical olympiads; problem solving